1992
DOI: 10.1159/000126224
|View full text |Cite
|
Sign up to set email alerts
|

Centrally Administered Insulin-Like Growth Factor II Fails to Alter Pulsatile Growth Hormone Secretion or Food Intake

Abstract: Insulin-like growth factor II (IGF-II) peptide, mRNA, and receptors are widely distributed in the central nervous system, yet the physiological role of IGF-II in brain remains largely unknown. In the present study, we examined the in vivo effects of central administration of recombinant human IGF-II on pulsatile GH secretion and food intake. The IGF-II preparation used was shown to stimulate 3H-thymidine incorporation in MG-63 human osteosar-coma cells in vitro. Free-moving adult male rats bearing chronic intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…These findings support the observation of Spencer et al (1991 and and Tannenbaum (1992a and1992b), who were unable to demonstrate a central effect of IGF-I on GH secretion and suggested that IGF-I does not play a role in the negative feedback regulation of GH at the level of the brain. To that extent, Fletcher et al (1995) was unable to demonstrate an inhibitory response to IGF-I following either lateral or third ventricle administration or infusion of 5 mg of IGF-I into the third ventricle over a 2 h period.…”
Section: Discussionsupporting
confidence: 89%
“…These findings support the observation of Spencer et al (1991 and and Tannenbaum (1992a and1992b), who were unable to demonstrate a central effect of IGF-I on GH secretion and suggested that IGF-I does not play a role in the negative feedback regulation of GH at the level of the brain. To that extent, Fletcher et al (1995) was unable to demonstrate an inhibitory response to IGF-I following either lateral or third ventricle administration or infusion of 5 mg of IGF-I into the third ventricle over a 2 h period.…”
Section: Discussionsupporting
confidence: 89%
“…Subse¬ quent studies showed that i.c.v. administration of human recombinant IGF-I (Harel & Tannenbaum, 19926) and IGF-II (Harel & Tannenbaum, 1992 ) in rats, did not affect pulsatile GH release, while a mixture was effective (Harel & Tannenbaum, 1992 ). The differences between early and recent studies on feedback effects on GH of IGF-I when administered centrally might be due to the IGF-I/somatomedin-C preparations being a mixture of IGF-I and IGF-II, while the recent development of recombinant technol¬ ogy has made large amounts of pure IGF-I and -II available.…”
Section: Discussionmentioning
confidence: 99%
“…Neither intracerebroventricular recombinant IGF-I (in doses up to 10 pg) nor IGF-I1 (at doses up to 1 Fg) affected GH secretion. Intriguingly, however, a dose of 1 pg IGF-I administered in conjunction with 1 pg IGF-I1 completely inhibited G H secretion (10,11). The synergy of centrally administered IGF-I and IGF-I1 in inhibiting G H secretion in rats supports the belief that the somatomedin-C preparations contained both IGF-I and IGF-I1 and emphasizes the importance of the hypothalamus in the regulation of G H secretion, possibly via somatostatin.…”
Section: Igf-i Regulation Of Gh Secretionmentioning
confidence: 74%